Washing rice before cooking has no large effect on the texture of cooked rice. (15th January 2019) - Li, Hongyan; Yang, Jingyuan; Gao, Muyao; Wang, Jing; Sun, Baoguo
Highlights: Statistic shows that washing times have no effects on hardness and stickiness. The washing procedure does not affect components and structure of leached material. This denies the hypothesis proposed by other researchers in a recent review paper. Abstract: Washing rice before cooking is common to remove dust and any remaining bran produced by the milling process. In this study, the effect of washing procedure on the textural properties of cooked rice, and its relations to starch leaching and the molecular structure of leached starch are investigated. Statistical analysis indicated that the washing procedure does not significantly affect either hardness or stickiness of cooked rice, but the interaction between rice variety and washing times on stickiness is significant. The components of leached materials, chain-length distribution (CLD), and molecular size of leached starch are significantly different from those of the surface materials, but not largely varied between rices with different washing times, which helps explain the molecular mechanism of the causes of these textural results. This indicates for the first time that, the adhering materials on the surface of raw rice grains do not contribute to the texture of cooked rice.